Representation of Arab Family Values in Short Stories As-Sinjabu Ash-Shogir by Kaamil Kailani: A Genetic Structuralism Study - Rian Muhamad Rian Nuryana; Marsha Marsha Meliana Putri; Anna Miftahul Khasanah; Robi Muhammad Robi; Akmaliyah Akmaliyah (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
This study analyzes the representation of Arab family values in Kamil Kaylani's short story As-Sinjabu As-Shoghir through Lucien Goldmann's genetic structuralism approach. This short story was chosen because it contains ideological tensions between traditional Arab values and the dynamics of modernity in the early 20th century. The analysis was conducted to reveal the dialectical relationship between narrative structure and social structure through the concept of human facts as a form of meaningful action in a social context. The method used was qualitative-descriptive with literary text analysis focusing on intrinsic elements and the configuration of human facts. The results of the study show that this short story represents the Arab patriarchal system as a fundamental fait social, with the father figure occupying the center of moral and social authority. The main values reproduced include ṭā‘ah (obedience) as the highest virtue, collective responsibility, patriarchal authority, female honor as a symbol of family morality, and the construction of knowledge as a threat to women. The text also displays ideological contradictions, particularly between isolation and protection and between women's moral ideals and their limited social space. These contradictions reflect the limited awareness of the modern Arab middle class, which seeks to preserve tradition while negotiating with modern values. Theoretically, this study confirms the function of children's literature as a medium for the reproduction of social ideology during the historical transition phase of Arab society. Keywords: Genetic Structuralism, Arab Family Values, Kamil Kaylani